1994
DOI: 10.1159/000282609
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Problems of Urine Cytology on Initial Follow-Up after Intravesical Immunotherapy with Calmette-Guérin Bacillus for Superficial Bladder Cancer

Abstract: After transurethral resection or biopsy, patients with recurrent bladder cancer or in situ carcinoma were given topical immunotherapy with low-dose Calmette-Guérin bacillus (BCG). In the recurrence-free interval they were treated with BCG monthly for 1 year and then every 3 months for the next year. Cytological analysis was always performed concomitant with the administration of immunotherapy. In order to evaluate the therapeutic success, cytoscopy and biopsy were performed after the first cycle of BCG and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 6 publications
1
12
1
Order By: Relevance
“…Only a few investigators have reported urinary cytology findings after intravesical BCG instillation therapy and the findings were not consistent [15,16]. Mack and Frick [15] reported cytological changes in patients with recurrent bladder cancer and CIS after TUR or biopsy to include enlarged, hyperchromatic nuclei, increased prominent nucleoli, anisonucleosis, distorted nuclear/cytoplasmic ratio of urothelial cells besides significant increase in inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few investigators have reported urinary cytology findings after intravesical BCG instillation therapy and the findings were not consistent [15,16]. Mack and Frick [15] reported cytological changes in patients with recurrent bladder cancer and CIS after TUR or biopsy to include enlarged, hyperchromatic nuclei, increased prominent nucleoli, anisonucleosis, distorted nuclear/cytoplasmic ratio of urothelial cells besides significant increase in inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mack and Frick [15] reported cytological changes in patients with recurrent bladder cancer and CIS after TUR or biopsy to include enlarged, hyperchromatic nuclei, increased prominent nucleoli, anisonucleosis, distorted nuclear/cytoplasmic ratio of urothelial cells besides significant increase in inflammatory cells. They stressed that cytological changes Takashi/Schenck/Koshikawa/Nakashima/ Ohshima such as hyperchromasia and distorted nuclear/cytoplasmic ratio, which usually suggest the presence of tumors, impair the interpretation of cytology in patients treated with topical BCG therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the intense inflammatory reaction induced by BCG makes the interpretation of cystoscopic findings difficult because areas of erythema can represent either carcinoma in situ or inflammation. In addition, cytology interpretation is complicated by reactive changes in the cells that make it difficult to distinguish malignant from reactive nonneoplastic cells [28]. A recent study was conducted to determine if FISH could be used to assess response to treatment in patients with superficial bladder cancer receiving BCG or other intravesical therapy [29].…”
Section: Fish For Bladder Cancer Detectionmentioning
confidence: 99%
“…BCG induced cytological changes are readily detectable within the first 3 months after the last instillation, including enlarged, hyperchromatic nuclei with prominent nucleoli, anisocaryosis, a shifted nucleus-to-plasma ratio and an increase in granulocytes. 15, 16 In a subgroup of samples these changes may be interpreted as positive cytology. In a study of 75 patients with positive urinary cytology after a complete response to BCG for at least 1 year clinically detectable disease developed in 83%.…”
Section: Discussionmentioning
confidence: 99%